2014
DOI: 10.1080/07391102.2014.947326
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and comparative binding mechanism of piperine with human serum albumin and α-1-acid glycoprotein

Abstract: Human serum albumin (HSA) and α-1-acid glycoprotein (AGP) (acute phase protein) are the plasma proteins in blood system which transports many drugs. To understand the pharmacological importance of piperine molecule, here, we studied the anti-inflammatory activity of piperine on mouse macrophages (RAW 264.7) cell lines, which reveals that piperine caused an increase in inhibition growth of inflammated macrophages. Further, the fluorescence maximum quenching of proteins were observed upon binding of piperine to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 66 publications
1
36
0
Order By: Relevance
“…A significant change in these signals reflected tertiary structural alteration of the protein . The increase in the thermal stability of HSA in the presence of PM is due to stabilization of the PM–HSA complex by the noncovalent forces, which required higher temperature to be broken down . Such an increase in the thermal stability of HSA in the presence of ligand has been reported earlier …”
Section: Discussionmentioning
confidence: 52%
“…A significant change in these signals reflected tertiary structural alteration of the protein . The increase in the thermal stability of HSA in the presence of PM is due to stabilization of the PM–HSA complex by the noncovalent forces, which required higher temperature to be broken down . Such an increase in the thermal stability of HSA in the presence of ligand has been reported earlier …”
Section: Discussionmentioning
confidence: 52%
“…Serum albumins play an important physiological role in the transportation and delivery of various small molecule ligands . Furthermore, binding of small molecules to serum albumins may affect the absorption, distribution, metabolism, and excretion of those compounds in vivo . The blood levels of bisphenols in mammals are associated with acute toxicity and endocrine‐disrupting activity through influencing the circulation of compounds and increasing the plasma half‐life .…”
Section: Methodsmentioning
confidence: 99%
“…Our group has extensively studied the interaction of various phytochemicals with serum proteins, and has observed that most of the phytochemicals bind strongly to HSA, [10][11][12] but only some of them bind to AGP. 13,14 Andrographolide (ANDR) is a labdane diterpenoid, which is the main bioactive component of the medicinal plant Andrographis paniculata. 15 ANDR has been reported to have a wide range of biological activities, such as anti-inammatory, 16 anti-allergic, 17 anti-platelet aggregation, 18 hepatoprotective, 19 and anti-HIV properties.…”
Section: Introductionmentioning
confidence: 99%